2020
DOI: 10.1016/j.actamat.2019.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Role of twinning on the omega-phase transformation and stability in zirconium

Abstract: Group-IV transition metal zirconium is used in nuclear and chemical industries as a choice material for operating in extrem\e environments. At ambient-conditions, zirconium has a stable hexagonal-close-packed structure (α-phase), but under highpressures it transforms into a simple-hexagonal structure (ω-phase). Experimental studies involving high-pressures have reported retention of ω-phase upon recovery to ambient-pressures, which is undesirable since the ω-phase is brittle compared to the αphase. Understandi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…The deformation-induced ω phase can be studied in pure Ti and Zr through the application of high static pressures because the structure remains stable after the pressure is removed [10,11,[45][46][47][48]. This is true of β-Ti alloys as well as pure α-Ti.…”
Section: Deformation-induced ω Phasementioning
confidence: 99%
See 1 more Smart Citation
“…The deformation-induced ω phase can be studied in pure Ti and Zr through the application of high static pressures because the structure remains stable after the pressure is removed [10,11,[45][46][47][48]. This is true of β-Ti alloys as well as pure α-Ti.…”
Section: Deformation-induced ω Phasementioning
confidence: 99%
“…However, β-stabilizer concentration is not the only variable that affects deformation-induced ω phase formation. Grain size [26], processing route [50], and the existence of deformation twins [48] have been shown to affect the volume fraction of the ω phase. In static-pressure experiments, impurities such as O or N increased the pressure required to initiate deformation-induced ω phase formation [45].…”
Section: Classification Of ω Phasesmentioning
confidence: 99%
“…Wenk et al (2013), for instance, studied the α ↔ ω transition in Zr and found i) a martensitic mechanisms with (0001) α ∥(11 20 ) β and ii) remarkable orientation memory during the reverse transformation. This was then followed by further studies on the α ↔ ω transition in Zr and the mechanical properties of both phases (Yu et al 2015, Kumar et al 2020, with the aim to design Zr microstructure and strengthen its mechanical properties for high-pressure applications.…”
Section: Materials Sciencementioning
confidence: 99%
“…Titanium and zirconium, for instance, are hexagonal-closepacked metals under ambient conditions. Under high pressure, they transform to another hexagonal structure, the ω phase, which is not compact and for which mechanical properties are poorly constrained (Yu et al 2015, Kumar et al 2020. In other cases, high pressure has been used as a fine-tuning parameter for optimizing strength and grain sizes (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, they are utilized as fuel cladding, pressure tubes, fuel channels, and fuel spacer grids [5][6][7]. Zr exhibits a number of complex features relevant to these applications, such as competing slip systems for dislocation motion, multiple possible cleavage planes, several modes of twinning deformations, and a high-temperature hexagonal close-packed (hcp) to body-centered cubic (bcc) phase transformation [4,[8][9][10]. Experimental investigations provide important information about the real material behavior but probing the underlying mechanisms governing the atomic-scale phenomena is challenging.…”
Section: Introductionmentioning
confidence: 99%